MNEs and knowledge creation in Medellín’s emerging ICT hub - Gómez Lucía (Taylor & Francis, 2022)
This paper contributes to understanding the potential for localised knowledge creation that can be generated by multinational enterprise (MNE) entry into cities in the global South from both the MNE and the local economy’s perspectives. It presents a qualitative analysis of the activities of the MNE subsidiaries in the information and communication technology (ICT) sector in an emerging investment hub in Medellín, Colombia. The analysis differentiates between the MNEs’ local strategies to explore distinct configurations of MNE–local economy relations and their potential for unilateral or mutually beneficial knowledge creation. The findings suggest that the synergy between the MNE strategies and the evolving knowledge environment in the local economy increases the potential of the MNEs’ activities for interactive and mutually beneficial knowledge and capability creation with other local stakeholders. In Medellín, these effects predominantly concerned the market-seeking MNEs, not those seeking strategic assets, as expected by evidence in the literature. They also revealed how the specific MNE strategies tended to use and influence the creation of local knowledge resources, which helps shape policies that indiscriminately aim to attract all kinds of knowledge-intensive MNE activities to emerging investment hubs.